2017
DOI: 10.1016/j.nlm.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Extinction after fear memory reactivation fails to eliminate renewal in rats

Abstract: Retrieving fear memories just prior to extinction has been reported to effectively erase fear memories and prevent fear relapse. The current study examined whether the type of retrieval procedure influences the ability of extinction to impair fear renewal, a form of relapse in which responding to a conditional stimulus (CS) returns outside of the extinction context. Rats first underwent Pavlovian fear conditioning with an auditory CS and footshock unconditional stimulus (US); freezing behavior served as the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 103 publications
(177 reference statements)
3
16
0
Order By: Relevance
“…With regard to how this may influence PRE effects, research suggests that hippocampal-dependent fear memories may be less susceptible to PRE effects. For strongly-hippocampal dependent fear memories formed through contextual fear conditioning, PRE studies conducted in animals have had a cumulative small nonsignificant effect (Goode, Holloway-Erickson, & Maren, 2017;Kredlow et al, 2016).…”
Section: Potential Moderators Of Pre -The Role Of the Hippocampusmentioning
confidence: 99%
“…With regard to how this may influence PRE effects, research suggests that hippocampal-dependent fear memories may be less susceptible to PRE effects. For strongly-hippocampal dependent fear memories formed through contextual fear conditioning, PRE studies conducted in animals have had a cumulative small nonsignificant effect (Goode, Holloway-Erickson, & Maren, 2017;Kredlow et al, 2016).…”
Section: Potential Moderators Of Pre -The Role Of the Hippocampusmentioning
confidence: 99%
“…In this regard, it has been reported that the NMDAR partial agonist d-cycloserine (DCS) increases exposure therapy effects [34][35][36] , although the available data are inconclusive 37,38 and experimental animals as well as humans treated with DCS during extinction learning show substantial recovery of learned fear, suggesting that DCS may not prevent PTSD relapse [39][40][41][42] . These studies, together with several others, suggest that extinction can indeed be modulated by drugs, but not lastingly [43][44][45] . Our findings that SDIA memory is still able to assume control of behavior after www.nature.com/scientificreports/ undergoing an extinction procedure that generates an extinction memory resistant to spontaneous recovery, renewal and reinstatement but sensitive to recall-induced GluN2B-containing NMDAR-dependent destabilization indicate that it is this destabilization what enables the reappearance of avoidance, and lead us to propose that blockers of these receptors might be suitable tools to prevent PTSD relapse.…”
Section: Discussionmentioning
confidence: 60%
“…It is worth reiterating that the attenuation of fear memory observed following retrieval-extinction itself is fragile, with approximately one-third of replication attempts failing (Kindt and Soeter 2013;Goode et al 2017;Luyten and Beckers 2017) or producing data that are inconsistent with the reconsolidation-update account (Chan et al 2010). However, other studies have indicated that the mechanism underlying retrieval-extinction depends upon prediction error (Piñeyro et al 2013) or produces molecular changes consistent with the reconsolidation-update account (Clem and Huganir 2010).…”
Section: Calcineurin (Pp2b)mentioning
confidence: 99%